Pengaruh Kompres Hangat terhadap Penurunan Nyeri Dismenore Pada Remaja Putri di Wilayah Kerja Puskesmas Cempaka Arum - Neng Komariah; Pipih Napisah; Yeti Hernawati (Sekolah Tinggi Ilmu Kesehatan Dharma husada, 2024)
Abstract Dysmenorrhea is pain in the lower abdomen that spreads to the waist and thighs. The prevalence of dysmenorrhea in Indonesia is 64.25%, primary dysmenorrhea is 54.89%, and secondary dysmenorrhea is 9.36%. Dysmenorrhea can be overcome with non-pharmacological interventions, namely warm compresses. The purpose of this study was to determine the effect of warm compresses in reducing dysmenorrhea pain in adolescent girls. The research method used quasi-experimental with a nonequivalent control group design. The sampling technique used purposive sampling. The population was all adolescent girls who experienced primary dysmenorrhea on the second and third days. A total of 30 adolescent girls were divided into intervention and control groups consisting of 15 people per group. Univariate analysis describes the frequency and percentage distribution. Bivariate analysis used the Wilcoxon test. The results showed that most respondents before being given warm compresses in the intervention group were in the moderate pain scale category (73.3%) and after the mild category (100%). The results of the bivariate test for the intervention group showed a significance value of p value 0.000. Meanwhile, the control group before being given the pain scale intervention was in the moderate category (40%) and after the mild category (66.7%). The results of the bivariate test of the control group showed a significant p value of 0.083. The effectiveness of the treatment reduced the pain scale in the intervention group by 62% and the control group by 27%. Thus, the provision of warm compresses is more effective in reducing dysmenorrhea pain.